Acute Hemodynamic Index as a Predictor of In-Hospital Mortality in Mechanical Ventilated Acute Decompensated Heart Failure Patients - Kurniawan, Dea Arie; Anjarwani, Setyasih; Rizal, Ardian; Satrijo, Budi; Yogibuana, Valerinna (Heart Science Journal, 2023)
Background: The likelihood of a poor clinical outcome is significantly increased in patients with acute decompensated heart failure. Mechanical ventilation was necessary for 23% of ADHF patients receiving treatment. The simple parameters of blood pressure and heart rate have good accuracy and repeatability. The development of the Acute Hemodynamic Index allowed for the calculation of pulse pressure and heart rate to be used as a basis for predicting intrahospital mortality.Methods: The medical records of patients who received care at CVCU RSSA were used in this retrospective, single-center study. ROC analysis and multivariate regression analysis were used to evaluate the prognostic performance of AHI. Statistical significance was determined by the P value of 0.05 or lower.Results: 252 patients with heart failure and low ejection fraction had their data analyzed. Hospital mortality is 82 percent. The cut-off was 4.19 mmHg/bpm, which was the AHI value. 68.8% of patients with fatal illnesses had low AHIs ( 4.19 mmHgbpm). AHI > 4.19 mmHgbpm patients have a 9-fold increased risk of dying in the hospital than patients with low AHI. AUC: 0.825 [0.743-0.907]; sensitivity: 0.814; specificity: 0.689; AUC: 0.825 [0.743-0.907; p = 0.000]; demonstrate the high predictive power of AHI.Conclusion: AHI has a strong degree of association with the likelihood of dying in the hospital from acute decompensated heart failure.